Community Extension Profiling of the Teaching and Non-teaching Personnel of the University - Montebon, Richie; Bachanicha, Rafael; Monton, Melvin; Engkong, Jean Careen; Labana, Alladino (JPAIR Multidisciplinary Research, 2022)
Building a community that needs assistance from various organizations, such as academic institutions, is a way to carry out the mission of helping to improve not only the living conditions of the underprivileged but also to have a more significant impact on the morals and principles of the faculty and staff who participated community extension related activities. With relevant provisions of the Higher Education Act of 1994, or Republic Act No. 7722, passed in 1994, and the Commission on Higher Education Memorandum Order No. 48 Series of 1996, Institutions of higher learning are supposed to have a reliable community extension program. Through community-based research, the CARES program of the University of Cebu Lapu-Lapu and Mandaue Campus continued to uphold the spirit of service to the community. As guided by the Vision, Mission, Goals, and Objectives and following the philosophies of the organization, the CARES program was able to create the flagship of every department, and it has been the primary foundation for community service in the partner community. This study is a descriptive, quantitative research design that was conducted on the Faculty and Non-teaching personnel at the University of Cebu – Lapu Lapu and Mandaue Campus. This study's primary goal is to determine the profile of faculty and non-teaching volunteers, know the different programs and activities that they want to be involved in, and determine the reasons for participating in the program. Also, to propose a recommendation based on the result of the study.
Keywords: Social Science; social community extension; community service; community profiling; teaching and non-teaching; Mandaue City; Cebu; Philippines